Analisis Kesesuaian Praktik Jual Beli Online dengan Prinsip Ekonomi Syariah - Indarsih, Fajar (CV. Lentera Literasi Indonesia, 2025)
This study aims to analyze the conformity of online buying and selling practices with the principles of Islamic economic law (sharia). The background of this research is based on the increasing phenomenon of digital transactions through marketplaces and social media platforms, whose compliance with Islamic muamalah principles is not yet fully recognized. This research employs a descriptive qualitative approach with data collected through in-depth interviews, observation, and documentation. The informants include online business actors, Muslim consumers, and Islamic economics experts. The findings reveal that most online transactions are conducted without explicit contracts (akad) and complete product information, which may result in elements of gharar (uncertainty). Additionally, practices such as dropshipping without ownership of goods and the use of paylater systems contain elements of riba (usury). This indicates that several e-commerce practices are still not aligned with sharia principles such as clarity of contract, transparency, and fairness. This study recommends the importance of educating digital muamalah literacy and the active role of authoritative institutions in developing online transaction guidelines in accordance with sharia values.